N2O emissions from soil amended with cattle slurry under mediterranean conditions - Carneiro, J.P. (2014)
N2O emissions are affected by several factors, including type of fertilizer, edafo-climatic conditions and mitigation measures applied. A field experiment was carried out in central Portugal for two consecutive years, to evaluate the effect over soil N2O emissions originated from the application of cattle slurry (CS) to a double-cropping system producing maize and oats. The use of a nitrification inhibitor (DCD) was evaluated as emission mitigation measure. A mineral fertilizer treatment (MIN) and a Control were included and the DCD effects were tested together with MIN (MIN+DCD) and CS (CS+DCD). Total N input was equal for all fertilizing treatments (oat 80 kg N ha- 1; maize 170 kg N ha-1). N2O fluxes were measure on 165 sampling dates, using a photoacoustic spectroscopic infrared gas analyzer. The most important fluxes were observed 8- 10 days after fertilizer incorporation and during the following 20-40 days. Annual N2O-N losses were higher in the first year, with a wettest autumn and a warmer summer than usual. The highest values were measured with the use of mineral fertilizers (4.65 and 4.21 kg N ha-1 in MIN+DCD and MIN, respectively), which were 60-70% higher than those measured with slurry application or without fertilization (1.85, 1.55 and 1.33 kg N ha-1 in CS+DCD, CS and Control, respectively). Mean annual values of emission factor based on N application (EF) were 0.76, 0.63, 0.12 and 0.07%, in MIN+DCD, MIN, CS and CS+DCD, respectively. The DCD use, namely with mineral fertilizer, didn’t produce an evident effect on total N2O losses.